Would-Be Warriors Incidents of Jihadist Terrorist Radicalization in the United States Since September 11, 2001 - Jenkins, Brian Michael (RAND Corporation, 2010)
Between 9/11 and the end of 2009, 46 publicly reported cases of domestic radicalization and recruitment to jihadist terrorism occurred in the United States, 13 of them in 2009. Most of the would be jihadists recruited themselves into the terrorist role, assisting foreign terrorist organizations, joining jihad fronts abroad, and plotting attacks. The terrorist threat has pushed law enforcement toward prevention rather than post-event apprehension.